Investigation of Gifted Secondary School Students’ Assessment of the Nature of Science in Turkey - Gorgulu, Deniz; Unlu, Sahika (European Scientific Journal, ESJ, 2024)
The objective of this study is to uncover the NOS evaluations of students enrolled in Science and Art Centers in Türkiye. We conducted the research using a case study design, which is a qualitative research method. The study focuses on 60 gifted secondary school students who will continue their education at the Seljuk Science and Art Center in the 2022-2023 academic year. The study evaluated the nature of science among gifted students using the Nature of Science Assessment Scale.The data underwent a descriptive analysis. This study, aimed to evaluate the nature of science among gifted students, revealed that students typically presented perspectives that aligned with the nature of science. However, an examination of gifted students’ views on the structure of scientific knowledge revealed that most of them believed the views of scientists would not influence scientific knowledge. The study also revealed that gifted students primarily believed that scientists’ observations led to the emergence of scientific knowledge. From this point of view, it was concluded that there are gifted students who have views on the role of the scientist in the production of scientific knowledge and the basis of scientific knowledge that are not appropriate for the nature of science. In this context, we believe it’s crucial to implement certain activities targeted at enhancing the NOS evaluations of students within the research’s scope.